Evaluation of the Clinical Education Environment of Babol University of Medical Sciences Based on the DREEM Model (Educational Environment Assessment Tool of Dundee University) from the Point of View of Nursing Students in the Academic Year 1402 - seyedeh zeinab hosseini motlagh; MohammadReza Sarmadi; Maryam Ghaemi Amiri (آموزش پزشکی)
Background and Objective: In the present study, to evaluate the clinical training environment of nursing student of Babol University of Medical Sciences,we used the DREEM questionnaire to get a comprehensive view of the problems of the educational environment. Methods: The current study is descriptive-cross-sectional and the sample size includes 147 nursing student who were selected by census method. DREEM standard questionnaire was designed electronically and its link was made available to nursing student. The questionnaire has two parts; Demographic characteristics and the second part includes 50 item statements based on a five-point Likert scale. The value of Cronbach's alpha coefficient in the relevant data has been calculated as 0.95, which shows a very good reliability. Findings: The overall evaluation score of the educational environment was reported as 122.06 ± 30.40, which according to the interpretation of the questionnaire scores, the overall evaluation score from the students' point of view was medium to high, generally the highest score related to the area of ​​understanding of learning (29.93( and then the understanding of the educational atmosphere (29.35) and the lowest score was related to the understanding of scientific ability (19.64) and then the understanding of social conditions (16.74). In all areas, the third and fourth year students had the highest score and the second year students had the lowest score. Conclusion: According to the obtained results, the clinical educational environment from the point of view of nursing students is medium to high, but in order to improve the conditions, it is necessary to review the educational plans and solve the problems that the students encountered